A Comprehensive Review of Electric Charging Stations with a Systemic Approach - Ricardo Tejeida-Padilla; Edgar Manuel Berdeja-Rocha; Isaías Badillo-Piña; Zeltzin Pérez-Matamoros; Juan Erick Amador-Santiago (World Electric Vehicle Journal)
Recently, the operation of electric charging stations has stopped being solely dependent on the state or centralised energy companies, instead depending on the decentralization of decisions made by the operators of these stations, whose goals are to maximise efficiency in the distribution and supply of energy for electric vehicles. Therefore, the operations of charging stations are exposed to increased complexity, leading to a growing need for decision-making based on more reliable and sustainable models. This research presents a review of key aspects, technologies, protocols, and case studies on the current and future trends of electric charging stations. A taxonomy of the technologies applied to charging stations and their applications in elements such as intelligent energy supply, electric vehicles, sustainability, the Industrial Internet of Things, and energy demand management is developed. Thus, this work synthesizes the essential features found in recent research regarding charging stations, aiming for a systemic approach that can lead toward sustainability in electromobility.